Immunotherapeutic approaches in nasopharyngeal carcinoma. (2nd November 2019) - Chow, James CH; Ngan, Roger KC; Cheung, KM; Cho, William CS
ABSTRACT: Introduction : Nasopharyngeal carcinoma (NPC) is endemic in Southern China and Southeast Asia. Epstein-Barr virus (EBV) represents a unique etiological culprit in the poorly differentiated nonkeratinizing and undifferentiated subtypes. EBV antigens are expressed on tumor cells albeit in a restricted manner. Treatment options for recurrent or metastatic disease are limited. Nevertheless, emerging data from immunotherapy studies in NPC have shed light into their potential antitumor efficacy. Areas covered : This article reviews existing clinical evidence for different immunotherapeutic approaches for NPC, including adoptive cellular therapy, therapeutic cancer vaccines, and immune checkpoint inhibitors. Expert opinion : There is a growing understanding on EBV virology and the immune evasion mechanisms in NPC. Immunotherapeutic strategies leveraging these properties have shown encouraging efficacy and safety results in early-phase clinical studies. Moving forward, areas to be addressed include appropriate patient selection, optimal incorporation into standard treatment paradigms, biomarker identification, as well as the development of scalable and reproducible immune product generation processes.